The effectiveness of the tax system in promoting General revenues in Algeria -Analytical study 2000-2015. - Tereche, ATTALLAH; Souihe, Djamel (Milev Journal of Research and Studies, 2022)
Through this study we analyzed the evolution proceeds of tax revenue and its place in the General State budget and development of indicators of fiscal pressure and regular revenue coverage for expenses of the propulsion, And reached the low level of fiscal pressure outside, and the dominance of petroleum taxation to the budget during the study period 2000-2015, as a result of poor performance and ineffective tax system despite reforms since the year 1992.